2023
DOI: 10.1093/cvr/cvad102
|View full text |Cite
|
Sign up to set email alerts
|

Chronic SIRT1 supplementation in diabetic mice improves endothelial function by suppressing oxidative stress

Abstract: Aims Enhancing SIRT1 activity exerts beneficial cardiovascular effects. In diabetes, plasma SIRT1 levels are reduced. We aimed to investigate the therapeutic potential of chronic recombinant murine SIRT1 (rmSIRT1) supplementation in diabetic mice (db/db) to alleviate endothelial and vascular dysfunction. Methods and Results Left-internal mammary arteries from patients undergoing coronary artery bypass grafting (CABG) with or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…When the degree of oxidative stress upregulates apparently, the level of malondialdehyde (MDA) increases while the levels of superoxide dismutase (SOD) and glutathione (GSH) decrease 20 . NOX-4 is an oxidase, which can exacerbate levels of oxidative stress 21 . While SOD-2 is an antioxidant enzyme that can reduce the level of oxidative stress 22 .…”
Section: Discussionmentioning
confidence: 99%
“…When the degree of oxidative stress upregulates apparently, the level of malondialdehyde (MDA) increases while the levels of superoxide dismutase (SOD) and glutathione (GSH) decrease 20 . NOX-4 is an oxidase, which can exacerbate levels of oxidative stress 21 . While SOD-2 is an antioxidant enzyme that can reduce the level of oxidative stress 22 .…”
Section: Discussionmentioning
confidence: 99%
“…However, another study showed that SIRT1 promotes insulin secretion and pancreatic beta cell survival by interacting with FOXO, which can alleviate diabetes (35). Additionally, restoring aortic SIRT1 levels can significantly improve endothelial dysfunction and vascular compliance by enhancing eNOS activity and inhibiting NOX-associated oxidative stress (36). SIRT1 can improve vascular function in diabetes by deacetylating the 66-kDa Src homology 2 domain-containing protein (p66Shc) and reducing ROS production (37).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Therefore, regulating OS is an important entry point for the treatment of POI. As a nicotinamide adenine dinucleotide-dependent deacetylase, Sirt1 can regulate a wide range of physiological functions and is the main regulator of metabolism and anti-oxidative stress [ 17 ]. It has been reported that Sirt1 is expressed in OGCs of various species, and activation of Sirt1 helps to improve ovarian function [ 14 ].…”
Section: Introductionmentioning
confidence: 99%